2019
DOI: 10.1002/pon.5102
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived stress on hope in women with breast cancer and the role of psychological hardiness

Abstract: Objective Diagnosis and treatment of breast cancer are psychologically stressful events, and hope and hardiness have been found to be important constructs for women with breast cancer. Therefore, this research sought to examine the relationships of perceived stress and hardiness with hope, and the buffering role of hardiness in the link between perceived stress and hope among Iranian women with breast cancer. Methods Two hundred and twenty Iranian women with breast cancer from three hospitals completed online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…The result of this study showed a significant relationship between psychological hardiness and perceived social support, which prevents psychological distress to deal with stress among women with breast cancer. It means that the higher the level of perceived social support, the higher the psychological hardiness of women with breast cancer, which was consistent with several other studies [10][11][12][13][14][15], and no study was found inconsistent with this finding. Abdollahi et al showed the significance of hardiness in decreasing perceived stress impacts on hope and reported its clinical implications for health practitioners [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of this study showed a significant relationship between psychological hardiness and perceived social support, which prevents psychological distress to deal with stress among women with breast cancer. It means that the higher the level of perceived social support, the higher the psychological hardiness of women with breast cancer, which was consistent with several other studies [10][11][12][13][14][15], and no study was found inconsistent with this finding. Abdollahi et al showed the significance of hardiness in decreasing perceived stress impacts on hope and reported its clinical implications for health practitioners [15].…”
Section: Discussionsupporting
confidence: 90%
“…Hardiness traits among females with breast cancer are a buffer in perceived stress [15]. People with a high level of hardiness are possibly more capable of enduring the negative results of life stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of each question range from "0" (not at all) to "3" (nearly every day). Depression severity was classified into none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (> 15) according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition criteria. ISI is a self-assessment tool measuring the patient's perception of both nocturnal and diurnal symptoms of insomnia.…”
Section: Psychological Status Of Patients With Bc During Covid-19mentioning
confidence: 99%
“…A 4-point Likert scale is used to rate each item (eg, 0 ¼ none, 4 ¼ very severe), yielding a total score ranging from 0 to 28. The total score is interpreted as follows: absent of insomnia (0-7); subthreshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15)(16)(17)(18)(19)(20)(21); and severe insomnia (22)(23)(24)(25)(26)(27)(28). The IES-R, also a self-reported questionnaire, yields a total score (ranging from 0 to 88).…”
Section: Psychological Status Of Patients With Bc During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation